2005
DOI: 10.1002/pros.20190
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hypoxia‐inducible factor‐1α (HIF‐1α) polymorphism as a mutation in prostate cancer that prevents normoxia‐induced degradation

Abstract: The P582S HIF-1alpha is a stable variant and HIF-1alpha mutation is a mechanism for enhancing HIF-1alpha activity in human cancer. The recent identification of the identical P582S HIF-1alpha as a polymorphism suggests that this variant may increase tumor susceptibility or cause more aggressive biological behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 31 publications
2
90
0
Order By: Relevance
“…A recently published meta-analysis suggests that both the T allele and TT genotype were significantly associated with increased cancer risk [17]. Experimental data also support a functional role for the C-by-T substitution at the allele and homozygous genotype level [12,28,29]. We found that additivity was better fitted for metastasis but not to ADT resistance, even though the low number of patients carrying the TT genotype in metastasis analyses yielded a very wide CI, hence deserving careful interpretation.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A recently published meta-analysis suggests that both the T allele and TT genotype were significantly associated with increased cancer risk [17]. Experimental data also support a functional role for the C-by-T substitution at the allele and homozygous genotype level [12,28,29]. We found that additivity was better fitted for metastasis but not to ADT resistance, even though the low number of patients carrying the TT genotype in metastasis analyses yielded a very wide CI, hence deserving careful interpretation.…”
Section: Discussionsupporting
confidence: 57%
“…Concordantly, two large case-control studies from the United States of America and China also observed no risk for having PCa in carriers of this polymorphism [19,26], even though opposite results have been also reported [16,27]. The C-by-T substitution in the +1772 locus at the oxygen-dependent domain of the HIF1A gene results in a proline-to-serine substitution and was shown to stabilise HIF1A and enhance its activity as a transcription factor in both normoxia and hypoxia [12,28]. In agreement, albeit we hypothesised those carriers of T allele were more susceptible to have cancer, our data, together with other, suggest no influence in earlier stages of prostate cancer development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The investigated SNPs were selected as potentially clinically relevant polymorphisms based on previous studies (18)(19)(20)(21)(26)(27)(28). Genomic DNA was purified from whole blood using the NucloeSpin ® Tissue method according to the manufacturer's instructions (NucleoSpin Tissue, Macherey-Nagel, Germany; Feb 2001/Rev.…”
Section: Analysis Of Snpsmentioning
confidence: 99%
“…44 However, the P582S polymorphism has been found to be associated with other disease phenotypes, including decreased coronary artery collateralization in ischemic heart disease patients, lower exercise-induced oxygen consumption in patients age 60 and older, prostate carcinoma, head and neck cancer and type 2 diabetes. [45][46][47][48][49][50] …”
Section: Chuvash Polycythemia and The P582s Polymorphism In Hif-1αmentioning
confidence: 99%